2007
DOI: 10.1038/ng1960
|View full text |Cite
|
Sign up to set email alerts
|

Refining the impact of TCF7L2 gene variants on type 2 diabetes and adaptive evolution

Abstract: We recently described an association between risk of type 2diabetes and variants in the transcription factor 7-like 2 gene (TCF7L2; formerly TCF4), with a population attributable risk (PAR) of 17%-28% in three populations of European ancestry. Here, we refine the definition of the TCF7L2 type 2diabetes risk variant, HapB(T2D), to the ancestral T allele of a SNP, rs7903146, through replication in West African and Danish type 2 diabetes case-control studies and an expanded Icelandic study. We also identify anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
370
8
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(410 citation statements)
references
References 26 publications
25
370
8
7
Order By: Relevance
“…35) and has been replicated in subsequent studies in many different ethnicities. [8][9][10][11][12][13][14][15][16] The association of other newly emerged GWAS loci, such as IGF2BP2, CDKAL1, CDKN2A/B, HHEX, SLC30A8 and KCNJ11, was replicated in Japanese; 17,18 IGF2BP2, SLC30A8, HHEX, CDKAL1, CDKN2A/B and FTO in Asians from Hong Kong and Korea; 19 IGF2BP2, CDKAL1, CDKN2A/B, HHEX and SLC30A8 in Han Chinese; 20 and IGF2BP2, PPARG2 and FTO in Indian Sikhs. 21 More recently, a meta-analysis of three large GWA studies by the Diabetes Genetics Replication and Meta-analysis (DIAGRAM) Consortium identified six additional T2D loci (NOTCH2, THADA, ADAMTS9, JAZF1, CDC123/CAMKID and TSPAN8/LGRS) to be strongly associated with increased susceptibility to T2D with modest ORs (1.15À1.3).…”
Section: Introductionmentioning
confidence: 96%
“…35) and has been replicated in subsequent studies in many different ethnicities. [8][9][10][11][12][13][14][15][16] The association of other newly emerged GWAS loci, such as IGF2BP2, CDKAL1, CDKN2A/B, HHEX, SLC30A8 and KCNJ11, was replicated in Japanese; 17,18 IGF2BP2, SLC30A8, HHEX, CDKAL1, CDKN2A/B and FTO in Asians from Hong Kong and Korea; 19 IGF2BP2, CDKAL1, CDKN2A/B, HHEX and SLC30A8 in Han Chinese; 20 and IGF2BP2, PPARG2 and FTO in Indian Sikhs. 21 More recently, a meta-analysis of three large GWA studies by the Diabetes Genetics Replication and Meta-analysis (DIAGRAM) Consortium identified six additional T2D loci (NOTCH2, THADA, ADAMTS9, JAZF1, CDC123/CAMKID and TSPAN8/LGRS) to be strongly associated with increased susceptibility to T2D with modest ORs (1.15À1.3).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have reported a link between variants in the TCF7L2 gene and type 2 diabetes [1][2][3][4][5][6][7][8] and in a recent meta-analysis, rs7903146 of TCF7L2 was associated with type 2 diabetes with allelic odds ratios of 1.46, making it the single strongest known genetic risk factor for type 2 diabetes [9].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The present letter discussed published data from European and nonEuropean populations and postulated that an independent secondary signal tagged by the rs12255372 SNP is also present in the TCF7L2 gene. The author also discussed recent results that show the presence of multiple enhancers in the TCF7L2 gene, 6,7 and advanced the hypothesis that these enhancers are redundant and there is person-to-person variability in their use.…”
Section: Resultsmentioning
confidence: 85%
“…[8][9][10] However, a critical assessment of published results does not rule out the presence of an independent secondary signal. Helgason et al 8 carried out haplotype analysis of SNPs, rs7903146 and rs12255372, and the microsatellite DG10S478 (ie, the three markers that were initially found with the strongest association with T2D 11 ) in Danish and Icelandic populations, and concluded that rs7903146 is the most likely causal variant.…”
Section: Causal Variants In Tcf7l2mentioning
confidence: 99%